Una ley de silencio que rompe la inocencia: labor del docente respecto a la protección, prevención y denuncia del abuso sexual infantil (A.S.I.) (2013)
"In trying to find this specific grounds for incorporation as strategies that will help in reducing disinterest by some teachers and pursued taboo regarding ASI, showing an existing reality, if we turn away from this, we help increase the risks favor the occurrence of this social problem. To others in the development of this paper is to make clear the existing regulations ""Constitution, conventions, laws and decrees"" that protects the rights of children u / or adolescents, with the intention of also generating interest in the Company on knowledge and effectively protect the Defense of the Rights of children."